La presència del Regne de València en el món europeu del Renaixement - Batllori, Miquel (Caplletra. Revista Internacional de Filologia, 2015)
The author stresses the importance of the Borja family (mainly referring to the popes Calixto III and Alexandre VI) in the Italian as well as the European cultural and political context of the second half of the xvth century, and the beginning of the xvith century.